Introduction to Buddhist East Asia - Scott, Robert H.; McRae, James (SUNY series in Asian studies development, 2023)
Foreword / Peter D. Hershock -- Acknowledgments -- Introduction to Buddhist East Asia: Origins, Core Doctrines, Transmission, and Schools / Robert H. Scott and James McRae -- Part I. Creative Pedagogies for Teaching Buddhist East Asia: 1. Three Common Misconceptions about East Asian Buddhisms: On Women and Gender, Violence and Non-Violence, and Philosophy and Religion / Sarah A. Mattice -- 2. Meditation Iis the Embodiment of Wisdom: East Asian Chan and Zen Buddhism in the Philosophy Classroom / Elizabeth Schiltz -- 3. The Possibility and Costs of Responsibly Teaching East Asian and Buddhist Philosophy / Mark Wells -- 4. Brains, Blades, and Buddhists: Pedagogical Skirmishes at the Intersection of Philosophy of Mind, the Way of the Sword, and Buddhism / Jesús Ilundáin-Agurruza -- 5. Revitalizing the Familiar: A Practical Application of Dōgen's Transformative Zen / George Wrisley -- Part II. East Asia Buddhisms and the Humanities: Ethics, Art, and Politics: 6. The Finger that Points to the Earth: East Asian Buddhism as a Conceptual Resource for Environmental Philosophy / James McRae -- 7. Ecological Self-understanding in Chinese Buddhism: Investigating an Epistemic Virtue / Jesse Butler -- 8. Wisdom and Compassion in Chinul, Korean Seon Buddhism, and Postmodern Ethics / Robert H. Scott -- 9. The Lovelorn Lady and the Stony Monk: Women, Sexuality, and Imagination in the Kegon Engi Emaki / Sujung Kim -- 10. The Spirit of Shaolin on Screen: Buddhism and Cultural Politics in Chinese Cinema / Melissa Croteau and Xin Zhang -- 11. A Century of Critical Buddhism in Japan / James Mark Shields -- Glossary of East Asian Buddhist Terms -- List of Contributors -- Index.